2014
DOI: 10.1021/ef501591m
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Steam on the Release of Potassium, Chlorine, and Sulfur during Char Conversion, Investigated under Dual-Fluidized-Bed Gasification Conditions

Abstract: The corrosion and fouling of heat-transfer surfaces and the agglomeration of bed materials in fluidized beds are some of the ash-related problems caused by the transformation and release to the gas phase of ash-forming elements from biomass during thermochemical conversion processes. The magnitudes of these problems are largely dependent upon the release of potassium (K), chlorine (Cl), and sulfur (S) from the biomass. We investigated the effects of steam on the release of K, Cl, and S during char conversion, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
38
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(41 citation statements)
references
References 55 publications
3
38
0
Order By: Relevance
“…As a result, the char-K was mainly transformed into K 2 CO 3 , and part of K 2 CO 3 was released to the gas phase during the char combustion stage. On the other hand, with the oxidation reaction of organic matter combined with K, K in char-K may also be directly released into the gas phase in the form of K or KOH . Nevertheless, nearly 68% of the total K remained in ash was in the form of K 2 CO 3 after char combustion.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, the char-K was mainly transformed into K 2 CO 3 , and part of K 2 CO 3 was released to the gas phase during the char combustion stage. On the other hand, with the oxidation reaction of organic matter combined with K, K in char-K may also be directly released into the gas phase in the form of K or KOH . Nevertheless, nearly 68% of the total K remained in ash was in the form of K 2 CO 3 after char combustion.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, with the oxidation reaction of organic matter combined with K, K in char-K may also be directly released into the gas phase in the form of K or KOH. 40 Nevertheless, nearly 68% of the total K remained in ash was in the form of K 2 CO 3 after char combustion. This indicated that the majority of char-K was transformed into K 2 CO 3 during the char combustion stage.…”
Section: Resultsmentioning
confidence: 99%
“…At 800–900 °C, the vapor pressure of KCl is highly significant for evaporation. However, the compactness of the biochar is also one of the factors controlling the extent of evaporation of KCl from the biochar . The authors observed an increase in the release of both chlorine and potassium when the temperature of steam gasification of wheat straw biochar raised from 800 to 900 °C.…”
Section: Resultsmentioning
confidence: 99%
“…Under gasification conditions (reducing atmosphere and T = 600−1000 °C), while the Ca in the ash layer is in solid form, the K is likely to form gaseous compounds, such as KOH or KCl (with the latter being formed if the fuel contains a substantial amount of Cl). 33,34 Under conditions relevant to steam gasification, the K in these compounds can originate from various sources, such as Ca/K/Si systems, 35 Ca/K/P systems, 35 Al/K/Si systems, 36 K 2 CO 3 , 37 and K 2 SO 4 . 38 In the present work, three theoretically plausible explanations are proposed for how the catalytic elements in the activated olivine come into contact with char to catalyze char gasification (Figure 1): (1) The outer surface (the Ca-rich ash layer) of the activated olivine particle comes into contact with the external surface of the char particle (i.e., solid−solid contact).…”
Section: Activated Olivinementioning
confidence: 99%
“…As mentioned in section , char gasification can also be catalyzed through the use of active bed materials. Just as in the case of catalytic tar reduction, K or Ca (or a combination thereof) is likely to be responsible for the increase in char gasification rate when an active bed material is employed. Under gasification conditions (reducing atmosphere and T = 600–1000 °C), while the Ca in the ash layer is in solid form, the K is likely to form gaseous compounds, such as KOH or KCl (with the latter being formed if the fuel contains a substantial amount of Cl). , Under conditions relevant to steam gasification, the K in these compounds can originate from various sources, such as Ca/K/Si systems, Ca/K/P systems, Al/K/Si systems, K 2 CO 3 , and K 2 SO 4 …”
Section: Activated Olivinementioning
confidence: 99%